Unlocking the ecotourism environment: exploring music as a tool for cultural preservation and sustainable tourism development - Agus Cahyono; Fajry Sub'haan Syah Sinaga; Sunarto Sunarto; Udi Utomo; Syahrul Syah Sinaga (Gelar : Jurnal Seni Budaya, 2023)
This qualitative research study investigates the role of music as a catalyst for fostering sustainable tourism practices and contributing to the long-term social, economic, and environmental well-being of ecotourism destinations. The focus is on Truthung's musical performances in Magelang, which serve as reflections of local tourism potential and the surrounding natural environment, including the Borobudur Temple and the Merapi, Merbabu, Andong, Sumbing, and Menoreh Mountains. Drawing upon the interdisciplinary concept of ecomusicology, this study employs various data collection methods, including observations, interviews, and documentation. By examining the growth and development of Truthung Music performances, with a particular emphasis on key figures such as Sutanto Mendut and farming artists from Merbabu, this research sheds light on the transformative power of music within the local community. The findings reveal that Truthung Music not only represents the rich local environment and culture within tour packages in Magelang Regency but also emphasizes the broader interplay between nature and culture. "Village Civilization" provides clear evidence of the relationship between nature and culture, showcasing the local potential of the Lima Gunung arts community. This research addresses a gap in the literature by examining the specific role of music in the context of ecotourism and its contributions to sustainable practices. The implications extend beyond the local community, providing valuable insights for policymakers, tourism professionals, and cultural preservationists regarding the significant role that music can play in promoting sustainable tourism and preserving the cultural heritage of ecotourism destinations.